A STUDY OF LINGUISTIC FEATURES OF PROVERBS EXPRESSING RICHNESS AND POVERTY IN ENGLISH VERSUS VIETNAMESE - Ph.D. HỒ THỊ KIỀU OANH (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2025)
This paper is aimed to: 1. Study proverbs in English and Vietnamese that expressing richness and poverty, and find out their syntactic and semantic features. 2. Find out similarities and differences between these proverbs in the two languages in terms of syntax and semantics in English and Vietnamese proverbs.